Safety of Tetanus Toxoid, Reduced Diphtheria Toxoid, and Acellular Pertussis and Influenza Vaccinations in Pregnancy. Issue 5 (November 2015) - Sukumaran, Lakshmi; McCarthy, Natalie L.; Kharbanda, Elyse O.; Weintraub, Eric S.; Vazquez-Benitez, Gabriela; McNeil, Michael M.; Li, Rongxia; Klein, Nicola P.; Hambidge, Simon J.; Naleway, Allison L.; Lugg, Marlene M.; Jackson, Michael L.; et al.
Abstract : OBJECTIVE: To evaluate the safety of coadministering tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) and influenza vaccines during pregnancy by comparing adverse events after concomitant and sequential vaccination. METHODS: We conducted a retrospective cohort study of pregnant women aged 14–49 years in the Vaccine Safety Datalink from January 1, 2007, to November 15, 2013. We compared medically attended acute events (fever, any acute reaction) and adverse birth outcomes (preterm delivery, low birth weight, small for gestational age) in women receiving concomitant Tdap and influenza vaccination and women receiving sequential vaccination. RESULTS: Among 36, 844 pregnancies in which Tdap and influenza vaccines were administered, the vaccines were administered concomitantly in 8, 464 (23%) pregnancies and sequentially in 28, 380 (77%) pregnancies. Acute adverse events after vaccination were rare. We found no statistically significant increased risk of fever or any medically attended acute adverse event in pregnant women vaccinated concomitantly compared with sequentially. When analyzing women at 20 weeks of gestation or greater during periods of influenza vaccine administration, there were no differences in preterm delivery, low-birth-weight, or small-for-gestational-age neonates between women vaccinated concomitantly compared with sequentially in pregnancy. CONCLUSION: Concomitant administration of Tdap and influenza vaccines during pregnancy was not associated with a higher risk of medically attended adverse acute outcomes or birth outcomes compared with sequential vaccination. LEVEL OF EVIDENCE: II Abstract : Concomitant tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis and influenza vaccination during pregnancy is not associated with a higher risk of adverse acute events or birth outcomes compared with sequential vaccination.